Ciliary photoreceptors with a vertebrate-type opsin in an invertebrate brain - Arendt, Detlev; Wittbrodt, Joachim (Science, 2004)
For vision, insect and vertebrate eyes use rhabdomeric and ciliary photoreceptor cells, respectively. These cells show distinct architecture and transduce the light signal by different phototransductory cascades. In the marine rag-worm Platynereis, we find both cell types: rhabdomeric photoreceptor cells in the eyes and ciliary photoreceptor cells in the brain. The latter use a photopigment closely related to vertebrate rod and cone opsins. Comparative analysis indicates that both types of photoreceptors, with distinct opsins, coexisted in Urbilateria, the last common ancestor of insects and vertebrates, and sheds new light on vertebrate eye evolution. The presence of an analog of a vertebrate eye in a primitive worm suggests that prototypes of both insect and vertebrate eyes existed in their last common ancestor.The presence of an analog of a vertebrate eye in a primitive worm suggests that prototypes of both insect and vertebrate eyes existed in their last common ancestor.